Balloon Pulmonary Angioplasty for the Treatment of Chronic Thromboembolic Pulmonary Hypertension - Lauren N. Carlozzi; C. Huie Lin; Zachary L. Steinberg (Methodist DeBakey Cardiovascular Journal)
Chronic thromboembolic pulmonary hypertension is a rare form of pulmonary hypertension in patients who have evidence of chronic thromboembolic occlusion of the pulmonary vasculature. Historically, surgical pulmonary thromboendarterectomy has been the treatment of choice. However, with up to 40% of patients deemed inoperable, balloon pulmonary angioplasty has emerged as an additional treatment strategy. Balloon pulmonary angioplasty is a complementary strategy alongside surgical pulmonary thromboendarterectomy and offers the opportunity for pulmonary revascularization in patients who have more distal disease, higher comorbidities, or residual obstruction following operative intervention. This review examines the history of balloon pulmonary angioplasty, highlights its effectiveness, discusses important complications and risk reduction strategies, and emphasizes the importance of centers forming a multidisciplinary team of providers to manage the complexity of patients with chronic thromboembolic pulmonary hypertension.